The Influence of Green Beans and Fe Tablets to Increasing Hb Levels of Pregnant Women in Cilamaya Wetan Health Center in 2022 - Lilis Iryani; Rahayu Khairiah (STIKep PPNI Jawa Barat, 2023)
Aims: To determine the effect of giving Fe tablets and mung bean juice on increasing Hb levels of pregnant women at the Cilamaya Wetan Public Health Center, Cilamaya Wetan Village in 2022. Methods: This study used a quasi-experimental research design with a pre-test and post-test approach, with divided into 2 groups, with the sampling method in this study using the quota sampling technique, namely the entire population was sampled, all of them were as many as 48 people. The data collection tool is using a questionnaire. The data collection technique used the square test with the help of SPSS version 28. Results: Obtained from 48 respondents who were divided into two groups where after being given fe tablets there was an increase in Hb, as well as respondents who were given mung bean juice had an increase in Hb levels. Where the results of the T-test (paired sample test) obtained a p-value of <.001. Conclusion: From the results of the study, it was found that there was an effect of giving Fe tablets and mung bean juice on the increase in Hb levels in pregnant women in the Cilamaya Wetan Public Health Center in 2022.